Chapter Der Verbalaspekt in der obersorbischen Umgangssprache im Sprachkontakt - Scholze, Lenka (Biblioteca di Studi Slavistici, 2023)
This paper deals with the Upper Sorbian aspect categories. While the traditional inflectional opposition imperfect vs. aorist is still widely used in the standard variety, it has almost disappeared from the colloquial variety used in the Catholic area of Upper Lusatia in Eastern Germany. By contrast, the derivational opposition of perfectivity formally persists in this area but has undergone some changes which are very specific to this variety. In particular, this aspect opposition, expressed by means of prefixes and suffixes has been radically restructured, such that its functional domain has shifted from grammatical aspect to grammatical telicity. It is argued that the starting point of this change is to be sought in an identification of the Sorbian aspect-sensitive grammatical prefixes with the German prefixes which mainly express telicity in processes of word formation. Special usages dealt with in this study are, on the one hand, the expression of habituality through (formally) imperfective verbs and, surprisingly, the expression of ongoing telic processes, but also of the analytical future, by means of their perfective correlates, on the other.